THE ROLE OF THE HOST IN MAKING A DOCUMENTARY FILM ENTITLED "THE CULTURE OF BATAK TOBA" - Chaerani, Chaerani; Atmaja, Suhendra (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to explore and analyze the role of the host in the production of the documentary film titled "The Culture of Batak Toba" in supporting the tourism sector in Samosir Island. The main focus of this research is on how the host can effectively convey messages from the sources to the audience and how the local wisdom of Batak Toba culture can be promoted through this documentary film. The method used in this research is qualitative, with data collection techniques through observation and interviews. Observations were carried out by visiting the communities around Samosir Island and the sources, while interviews were conducted with key stakeholders directly involved in this film, including archaeologists, the Toba Caldera development coordinator (UNESCO), the Secretary of North Sumatra, and the deputy for systems and strategy at BNPB. The results of the research show that the role of the host is crucial in ensuring the smooth production of the documentary film. The host must have good communication skills, master the subject matter, and be able to build good relationships with the sources. This documentary film also successfully highlights the disaster-aware culture of the Batak Toba community, which is expected to raise awareness about the importance of environmental conservation and improve services to tourists. In conclusion, the host plays a vital role in the production of the documentary film, not only as a communicator between the sources and the audience but also in ensuring that the conveyed messages are well received.